Business Continuity Management BETH3 (Building, Equipment, Technology, Human Resources and 3rd Party) : A Conceptual Framework in Banking Sector - Hadiwibowo, Arief; Pranata Ganda Dimulya, Aditya; Arum Handayani, Gabriela; Jauhari, Tantowi; Hanggraeni, Dewi (Jurnal Pendidikan Indonesia, 2025)
This study analyzes the challenges of Business Continuity Management (BCM) for the banking sector, especially conventional commercial banks in facing various operational challenges. BCM serves as a framework to help minimize the impact of disruption on the banking sector in the face of risks such as natural disasters, pandemics, and cyberattacks. The methods used include Business Impact Analysis (BIA), development of recovery strategies, and implementation of sustainable mitigation measures with the implementation of the BETH3™ framework and international standards such as ISO 22301, so as to provide systematic guidance in identifying critical assets and designing integrated mitigation measures, which include building elements, equipment, technology, human resources, and third parties in the bank Conventional. The results of the study show that BCM not only allows the banking sector to survive and adapt to the crisis, but also accelerates operational recovery. With a focus on continuous improvement, the implementation of the BETH3™ framework in BCM can prepare the Bank to face challenges more prepared and adaptive. The need for stronger collaboration with external parties, such as regulators and technology providers, as well as the importance of regular training for employees to ensure readiness to deal with crisis situations. Thus, the banking sector can be better prepared to face challenges and maintain competitiveness in a dynamic market